2005
DOI: 10.1016/j.cub.2005.02.051
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of a Yeast LTR Retrotransposon by Human APOBEC3 Cytidine Deaminases

Abstract: The mammalian APOBEC3 family of cytidine deaminases includes several members that possess potent antiretroviral activity. Human APOBEC3F and APOBEC3G are specifically incorporated into human immunodeficiency virus type 1 (HIV-1) progeny virions in the absence of virion infectivity factor (Vif), where they deaminate deoxycytidine to deoxyuridine on the minus strand of nascent reverse transcripts. Editing of the HIV-1 cDNA leads to its degradation or to G to A hypermutation of the integrated provirus. Here, we s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
126
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 123 publications
(132 citation statements)
references
References 39 publications
6
126
0
Order By: Relevance
“…Investigation of the sequences surrounding the edited nucleotides revealed dominance of adenosines at position + 2 relative to the editing site (GxA→AxA motif; the underlined G is the editing site; Methods and Supplementary Table S1). This is in agreement with previous experimental studies [14][15][16][17][18][19][20]23,24 and supports the identification of these mismatches as an outcome of mouse APOBEC3 activity.…”
Section: Identification Of Editing Sitessupporting
confidence: 93%
See 1 more Smart Citation
“…Investigation of the sequences surrounding the edited nucleotides revealed dominance of adenosines at position + 2 relative to the editing site (GxA→AxA motif; the underlined G is the editing site; Methods and Supplementary Table S1). This is in agreement with previous experimental studies [14][15][16][17][18][19][20]23,24 and supports the identification of these mismatches as an outcome of mouse APOBEC3 activity.…”
Section: Identification Of Editing Sitessupporting
confidence: 93%
“…This process is thus called DNA editing. In recent years, it was shown that active LTR (long terminal repeat) retrotransposons, which are endogenous retroviruses, can also be edited [14][15][16][17][18][19][20][21] . However, the impact of DNA editing on genome variability has not been explored to date 22 .…”
mentioning
confidence: 99%
“…8,9 The cytidine deaminase APOBEC3G (A3G), which is encoded within a cluster of seven related editing enzymes (APOBEC3A-G) on chromosome 22, provides broad innate immunity against exogenous and endogenous retroelements. [10][11][12][13][14][15][16] Encapsidated into the retroviral particle A3G deaminates dCs of the retroviral minus strand cDNA immediately on reverse transcription within the infected cell, and the formation of dUs leads to premature degradation of the retroviral cDNA or to non-functional hypermutated proviruses. [10][11][12][13][14][15][16] HIV overcomes this innate defense barrier in T-cells with the help of the HIV-encoded Vif (virion infectivity factor) protein that specifically targets A3G to proteosomal degradation.…”
mentioning
confidence: 99%
“…[10][11][12][13][14][15][16] Encapsidated into the retroviral particle A3G deaminates dCs of the retroviral minus strand cDNA immediately on reverse transcription within the infected cell, and the formation of dUs leads to premature degradation of the retroviral cDNA or to non-functional hypermutated proviruses. [10][11][12][13][14][15][16] HIV overcomes this innate defense barrier in T-cells with the help of the HIV-encoded Vif (virion infectivity factor) protein that specifically targets A3G to proteosomal degradation. [17][18][19] In addition, the editing enzymes APOBEC3F (A3F) and APOBEC3B (A3B) inhibit HIV-1, and A3B and APOBEC3C (A3C) restrict simian immunodeficiency virus replication by cytidine deamination of the viral minus strand cDNA, and A3B and to a lesser extent also A3F are resistant to HIV Vif-induced proteosomal degradation.…”
mentioning
confidence: 99%
“…hA3G has received considerable attention as an innate mechanism of cellular defense against retroviral infection and as a potential target for antiretroviral therapy. While it is clear that hA3G can counteract multiple retroviruses as well as retrotransposons in vitro (6,7,15,22), its usefulness as a clinical marker of infection remains unclear. Further studies to elucidate the clinical utility of hA3G and hA3F may include the examination of CD4 ϩ T cells rather than PBMCs and follow a larger cohort over time to examine the predictive relationship on progression to AIDS.…”
mentioning
confidence: 99%